1998
DOI: 10.1055/s-0037-1615105
|View full text |Cite
|
Sign up to set email alerts
|

The 4G/5G Sequence Polymorphism in the Promoter of Plasminogen Activator Inhibitor-1 (PAI-1) Gene: Relationship to Plasma PAI-1 Level in Venous Thromboembolism

Abstract: SummaryImpaired fibrinolysis due to increased plasminogen activator inhibitor-1 (PAI-1) is observed in up to 40% of patients with venous thromboembolism and might be causally related to the disease. There is evidence that genetic variations in the promoter of the PAI-1 gene and metabolic factors contribute to increased plasma PAI-1 levels.A single nucleotide insertion/deletion (4G/5G) polymorphism in the promoter region of the PAI-1 gene and metabolic factors were studied in 158 unrelated patients below the ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
3
5

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(84 citation statements)
references
References 25 publications
4
72
3
5
Order By: Relevance
“…The reported prevalence of the PAI-1 polymorphism for homozygous 4G/4G was 17% [45]. Among 4G/4G, 5G/5G and 4G/5G genotypes, the highest PAI-1 activity was observed in 4G/4G [44]. 4G/5G allele distribution is similar in patients with thrombosis and healthy subjects.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The reported prevalence of the PAI-1 polymorphism for homozygous 4G/4G was 17% [45]. Among 4G/4G, 5G/5G and 4G/5G genotypes, the highest PAI-1 activity was observed in 4G/4G [44]. 4G/5G allele distribution is similar in patients with thrombosis and healthy subjects.…”
Section: Discussionmentioning
confidence: 87%
“…Up to 40% of patients with venous thromboembolism exhibit impaired fibrinolysis due to increased plasminogen activator inhibitor-1 (PAI-1). The 4G/4G genotype contributes as an additional risk factor to the development of thromboembolic events [43,44]. The reported prevalence of the PAI-1 polymorphism for homozygous 4G/4G was 17% [45].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that the 4G/4G genotype contributes as an additional risk factor to the development of myocardial infarction [28], arterial [29] and venous thrombosis [30]. The reported prevalence of the PAI-1 polymorphism for 4G/5G was 51% and for homozygous 4G was 17% [31].…”
Section: Discussionmentioning
confidence: 99%
“…Ein Polymorphismus in der Promotorregion des für PAI-1 kodierenden Gens an der Stelle 4/5-Guanin moduliert die Plasmaaktivität dieser Substanz [47,64,75] und wird in neueren Untersuchungen mit der Entwicklung atherosklerotischer und thromboembolischer Erkrankungen in Verbindung gebracht [23,36,47,64].…”
Section: Das Fibrinolytische Systemunclassified